Analysis of the Nature of the Fulfillment of the Obligation in Iran and in France Civil Codes - Zahra Babajani; Saeid Kheradmandy; Mohamad Javad Jafari (Jurnal Cita Hukum, 2019)
AbstractCompletion of ambiguity and the provision of accurate legal interpretations requires the examination of various legal opinions. Legal rights regarding ambiguity are contained in Article 265 of the Iranian Civil Code which states that if someone gives property to someone else, it is assumed that he has not done it without consideration. This has been a matter of years of debate between lawyers. Some of them considered the problem as proof that someone who gave property was compulsory, and they believed that the request for expropriation of property must prove that there was no obligation to give and deserve to receive repayment of the property. Others believe in the lack of certainty of the obligations of the giver and require proof of the right to accept the recipient of the property. The findings of this study indicate that what caused the disagreement in the court was due to the Brief Article of the Civil Code of Iran, and a lack of attention to the legislator's ultimate goals in the public interest, and a lack of understanding of the difference between "giving property" and "paying money to others. "Among the legal experts made an interpretation of Article 265 of the Iranian Criminal Code and adapted it to Article 1235 of the French Criminal Code, because this provision does not say that anyone who provides financial assistance to someone is considered that he did not do so without consideration, so he could return it. The result of this deduction is "praduga Juris tantum" which will persuade the judge's conscience.Keywords: Payment, Compliance with Obligations - Without Appeal Juris Tantum's Considerations Abstrak:Penyelesaian ambiguitas dan pemberian interpretasi hukum yang akurat memerlukan pemeriksaan berbagai pendapat hukum. Hak-hak hukum mengenai ambiguitas tertuang dalam Pasal 265 KUH Perdata Iran yang menyatakan bahwa jika seseorang memberikan properti kepada orang lain, maka itu dianggap dia belum melakukannya tanpa pertimbangan. Hal ini telah menjadi masalah perdebatan selama bertahun-tahun antara pengacara. Beberapa dari mereka menganggap masalah tersebut sebagai bukti bahwa seseorang yang memberikan properti wajib, dan adanya permintaan untuk pengambilalihan properti harus terbukti tidak adanya kewajiban untuk memberi dan pantas menerima pembayaran kembali properti itu. Sebagian lain percaya pada kurangnya kepastian kewajiban pemberi dan membutuhkan bukti hak untuk menerima pada penerima properti. Temuan penelitian ini menunjukkan bahwa penyebab perdebatan di pengadilan karena ambiguitas pasal Ringkas pada Kode Sipil Iran, dan kurangnya perhatian terhadap tujuan akhir legislator untuk kepentingan publik, serta kurangnya pemahaman akan perbedaan makna antara "memberi properti" dan "membayar uang kepada yang orang lain." Para ahli hukum melakukan penafsiran terhadap Pasal 265 KUHP Iran dan melakukan adaptasinya dengan Pasal 1235 KUHP Perancis. Hasil dari deduksi ini adalah "praduga juris tantum" yang akan dapat mempengaruhi hati nurani hakim.Kata kunci: Pembayaran, Pemenuhan Kewajiban Tanpa Banding, Anggapan Juris Tantum Аннотация:Кодекс поведения, который предусматривает: «если кто-то передает имущество другому, это считает, что он не сделал это без рассмотрения; ... "и сравнивает его с французским законодательством, которое на протяжении многих лет было предметом спора между юристами. Некоторые из них считают эту статью доказательством того, что лицо, передающее имущество, является обязанным, и считают, что запрос об экспроприации имущества должен доказать, что выкуп имущества не является обязательным, но другие считают, что отсутствие определенности в отношении обязанности дарителя и требование подтверждения принятия для получения на имущество получателя. Исследование показывает, что противоречивые мнения в судах обусловлены: 1- краткой статьей 265 гражданского кодекса ирана. 2. Отсутствие внимания к конечной цели законодателя в общественных интересах. 3. Отсутствие различия между «передачей имущества» и «выплатой денег другому» в уголовном кодексе ирана и его адаптацией к статье 1235 уголовного кодекса франции. Результатом этого является «презумпция juris tantum», которая убедит совесть судьи.Ключевые Слова: Оплата, Исполнение Обязательства Без Рассмотрения Апелляционно-Презумпционной Юрисдикции